2018
DOI: 10.1108/imefm-05-2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance quality of Islamic banks: measurement and effect on financial performance

Abstract: Purpose This paper aims to assess the measurement of the Corporate Governance (CG) quality of Islamic Banks (IBs) and its effect on financial performance. Design/methodology/approach In the applied part of this study, a sample of 44 IBs operating in Bahrain, Kuwait, Qatar, Oman, the United Arab Emirates and the Kingdom of Saudi Arabia were investigated according to information provided by the national central bank websites of the Gulf Cooperation Council (GCC) countries. To measure the governance quality, CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
9
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 61 publications
12
106
9
3
Order By: Relevance
“…Because many of the small numbers of audits will continue to supervise financial statements. This finding supports research conducted by Ajili and Bouri (2018), but the results of this study cannot support the research of Taufiq et al (2014).…”
Section: The Audit Committee Did Not Affect Financial Performancecontrasting
confidence: 59%
“…Because many of the small numbers of audits will continue to supervise financial statements. This finding supports research conducted by Ajili and Bouri (2018), but the results of this study cannot support the research of Taufiq et al (2014).…”
Section: The Audit Committee Did Not Affect Financial Performancecontrasting
confidence: 59%
“…The existing governance framework of the Islamic banks is at least different in theory from the conventional counterpart by a commitment to social justice [11]. The authors of [38] argued that the introduction of Islamic principles and laws makes it different from the conventional corporate governance structure. Islamic corporate governance has two main aspects.…”
Section: The Moderating Role Of Islamic Corporate Governance On the Lmentioning
confidence: 99%
“…The SSB represents the total number of members available in the Shariah supervisory committee of the Islamic banks. The SSB has main three roles that are the consulting, controlling, and ensuring [38]. According to the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), the preferred minimum number of the SSB is three.…”
Section: The Moderating Role Of Islamic Corporate Governance On the Lmentioning
confidence: 99%
“…The research found that ownership structure is positive and significant on firm performance. The contrast, Ajili and Bouri (2018) found that good corporate governance had an insignificant association with high performance in GCG. Temesgen (2013), found that Good corporate governance namely a large board size tends to impact performance negatively.…”
Section: Introductionmentioning
confidence: 90%